2022
DOI: 10.1080/21655979.2022.2076009
|View full text |Cite
|
Sign up to set email alerts
|

Differences between the effects of plant species and compartments on microbiome composition in two halophyte Suaeda species

Abstract: Root-related or endophytic microbes in halophytes play an important role in adaptation to extreme saline environments. However, there have been few comparisons of microbial distribution patterns in different tissues associated with halophytes. Here, we analyzed the bacterial communities and distribution patterns of the rhizospheres and tissue endosphere in two Suaeda species ( S. salsa and S. corniculata Bunge) using the 16S rRNA gene sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The occurrence of Euzebya in these environments has been reported in numerous studies [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55], denoting the ability of the members of this genus to prosper in habitats with high salt concentrations (Table 2).…”
Section: Euzebyales In Extreme Environmentsmentioning
confidence: 68%
See 1 more Smart Citation
“…The occurrence of Euzebya in these environments has been reported in numerous studies [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55], denoting the ability of the members of this genus to prosper in habitats with high salt concentrations (Table 2).…”
Section: Euzebyales In Extreme Environmentsmentioning
confidence: 68%
“…In other highly saline environments, such as salt marshes, mines, and lake soils, Euzebya was detected in the rhizosphere of halophytic plants [41,43,[47][48][49]54].…”
Section: Euzebyales In Extreme Environmentsmentioning
confidence: 99%
“…They play a crucial role in nutrient cycling, organic matter decomposition, and enhancing plant resistance to abiotic and biotic stress to maintain productivity ( 37 ). However, the diversity and community structure of halophyte-associated rhizosphere microbes depend on the soil properties and plant species ( 38 ). Our research highlights the importance of understanding the complex interplay between soil properties, plant species, and microbial communities in saline soils.…”
Section: Discussionmentioning
confidence: 99%
“…It can be seen that not only related to soil characteristics, but also plant physiological activity can influence the microbial community structure. Plant species have been proved that it can affect the structural and functional diversity of rhizosphere microbial community due to variations in root exudation and rhizodeposition in different zones ( 38 , 46 ). In our study, we also confirmed this viewpoint and found significant differences in the structure of bacterial and archaeal community structures in the rhizosphere between S. altissima and S. dendroides ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The endophytic bacterial community's niche differentiation is low due to the host plant's space and nutrient limitations. Similarly, sediment microbial communities exhibit niche differentiation, which may result from root deposition effects, leading to the selection of specific bacteria combinations [42]. The networks of V. natans' various samples were positively correlated, indicating that most bacterial colonies had extensive cooperative and symbiotic potential in their respective compartments.…”
Section: Co-occurrence Network Of Bacterial Communities In Different ...mentioning
confidence: 99%